The Influence of History Learning and Student Perceptions General Soedirman's character in defending the country at SMAN 1 Rembang Purbalingga - Rahim, Tri Wardani; Bain, Bain (Indonesian Journal of History Education, 2022)
The study aims to determine the effect of the historical learning (Soedirman sub-material) and students' perception of General Sudirman's figure on the national defense attitude of grade XI students in Senior High School 1 Rembang Purbalingga. The type of this research is ex-post facto research. The population in this research was the eleventh-grade students in Senior High School 1 Rembang Purbalingga. The research sample was the eleventh-grade students consisting of 8 classes taken each of 21 children from each class with 168 students. The variables in this study consisted of independent variables, that is, the historical learning chapter of Soedirman (X1) and the student's perception of Soedirman 's figure (X2), and the dependent variable is the attitude toward defending the country (Y). The data collection methods used were questionnaires and documentation. Data analysis used descriptive percentage analysis and multiple regression analysis. The results showed that historical learning and students' perception of Soedirman 's figure affect their attitude toward defending the country. This is proven by test F obtained from Simultaneous learning of the history chapter of Soedirman and the student's perception of Soedirman 's figure with the attitude of defending the country equal to 34.8%.